Clinical biomarkers in soft tissue sarcoma A comprehensive review of current soft tissue sarcoma biomarkers. Issue 2 (29th September 2021) - Sharma, Soumya R.; Paonessa, Nadia E.; Casadei, Lucia; Costas De Faria, Fernanda; Pollock, Raphael E.; Grignol, Valerie
Abstract: Soft tissue sarcomas (STS) are a heterogeneous group of tumors that arise from mesenchymal tissue. Investigation at the molecular level has been challenging due to the rarity of STS and the number of histologic subtypes. However, recent research has provided new insight into potential genomic, proteomic, and immunological biomarkers of STS. The identification of biomarkers can improve diagnosis, prognosis, and prediction of recurrence and treatment response. This review provides an understanding of biomarkers, discussing the current status of biomarker research in STS.